Some factors affecting the longevity of Hungarian Simmental beef purposed cattle - Wissem BACCOURI; János POSTA (Journal of Central European Agriculture, 2025)
The study aimed to assess the influence of herd size, age at first calving, year, month, season of first calving, and first calf sex on the longevity of Hungarian Simmental beef cattle using survival analysis. The data included 598 sires, 9,077 dams, and 14,165 cows, with longevity defined by the number of calvings. A Weibull proportional hazards model was applied to analyse functional longevity. Results indicated the lowest culling risk (20% less) in cows calving first ≤ 27 months of age compared to the reference (33< and ≤ 36 months). Cows first calving at 46< months showed a 37% higher culling risk. Medium-sized herds had the highest culling risk (23%) compared to the reference, while large herds had the lowest. Seasonally, spring and summer calving presented higher risks, and a slight increase in culling risk was observed for cows with male first calves (0.4% higher). Findings show that these factors significantly affect longevity, making them valuable considerations for herd management. The heritability for calving number was h² = 0.20, suggesting that it is a useful selection trait due to its low heritability and reliable measurability, supporting its role in longevity enhancement.